Silk-Based Biomaterials for Designing Bioinspired Microarchitecture for Various Biomedical Applications - Kumar Sahi A.; Gundu S.; Kumari P.; Klepka T.; Sionkowska A. (My University, 2025)
Biomaterial research has led to revolutionary healthcare advances. Natural biological macromolecules can impact high-performance, multipurpose materials. This has prompted the quest for affordable healthcare solutions, with a focus on renewable biomaterials with a wide variety of applications and ecologically friendly techniques. Imitating their chemical compositions and hierarchical structures, bioinspired based materials have elevated rapidly over the past few decades. Bio-inspired strategies entail extracting fundamental components and reassembling them into programmable biomaterials. This method may improve its processability and modifiability, allowing it to meet the biological application criteria. Silk is a desirable biosourced raw material due to its high mechanical properties, flexibility, bioactive component sequestration, controlled biodegradability, remarkable biocompatibility, and inexpensiveness. Silk regulates temporo-spatial, biochemical and biophysical reactions. Extracellular biophysical factors regulate cellular destiny dynamically. This review examines the bioinspired structural and functional properties of silk material based scaffolds. We explored silk types, chemical composition, architecture, mechanical properties, topography, and 3D geometry to unlock the body’s innate regenerative potential, keeping in mind the novel biophysical properties of silk in film, fiber, and other potential forms, coupled with facile chemical changes, and its ability to match functional requirements for specific tissues. © 2023 by the authors.